Induction of Apoptosis with Silver Nanoparticles Obtained Using Thermophilic Bacteria - Kotryna Čekuolytė; Diana Šapaitė; Estera Žemgulytė; Renata Gudiukaitė; Eglė Lastauskienė (Journal of Functional Biomaterials, 2024)
Yeasts resistant to antifungals have become an increasing risk to human health. One of the best antimicrobial properties is reported to be present in silver nanoparticles (AgNPs); however, little is known about the antimicrobial potential of AgNPs produced using thermophilic bacteria. How AgNPs cause cell death is different depending on the type of the cell, and the mode of death induced is cell-type specific. Apoptosis, one of the types of regulated cell death, can be extremely useful in the fight against infection because surrounding cells that have phagocytic activity can efficiently absorb the apoptotic bodies formed during apoptosis. In the course of this work, for the first time, comprehensive antifungal studies of AgNPs were performed using thermophilic Geobacillus spp. bacteria against Candida guilliermondii, also with the addition of the model yeast Saccharomyces cerevisiae. The determined minimal inhibitory concentrations (MICs) were 10 μg/mL against C. guilliermondii and 50 μg/mL against S. cerevisiae for Geobacillus sp. strain 25 AgNPs, and for Geobacillus sp. 612 the MICs were 5 μg/mL and 25 μg/mL, respectively. It was shown for the first time that the exposure of the yeast cells leads to caspase activation in both S. cerevisiae and C. guilliermondii after exposure to Geobacillus spp. AgNPs. Also, a statistically significant change in the number of cells with permeable membranes was detected. Moreover, it was shown that the antimicrobial effect of the AgNPs is related to ROS generation and lipid peroxidation in C. guilliermondii yeast.